Non-transitive patterns in sports match outcomes: A profitable anomaly - Jan C. van Ours (Tinbergen Institute, 2025)
While sports betting markets share similarities with traditional financial markets, they are more accessible for empirical research thanks to availability of high-quality data, straightforward betting procedures, and the finite duration of events. As a result, they are often analyzed for market efficiency and serve as a field laboratory for studying financial markets. This study examines 24 seasons of English Premier League matches, revealing consistent non-transitive patterns in match outcomes among various triads (groups of three clubs). These empirical findings are difficult to rationalize and represent a notable anomaly. Bookmakers ignore the non-transitive patterns when setting odds. Faced with a trade-off between efficiency using historical information and maintaining consistency, they prioritize consistency.
Keywords: C25; D01; Z2; 330; Market efficiency; Sports betting; Non-transitivity; Football; English Premier League